Translation issues of social networks marketing terminology based on the Facebook ad manager service glossary - Ostapenko, Inna (Видавництво Львівської політехніки, 2017)
The vocabulary of untranslated English terms for Ukrainian version of Facebook Ad Manager was compiled. The ways of their translation into Ukrainian language were analyzed. The issue of Russian barbarisms in Ukrainian terminology was raised.
Keywords: Facebook Ad Manager; translation; electronic marketing; terminology